Analysis of Factors Affecting Audit Delay in Companies Listed on the Stock Exchange (Case Study at PT Envy Technologies Indonesia Tbk in 2021–2024) - Windayani; Nursam; Devy Nirwatul Khasanah; Syaqina Nurfadillah; Muchriana Muchran (www.amertainstitute.com, 2025)
This study aims to analyze the effect of financial distress, profitability, and earnings quality on audit delay at PT Envy Technologies Indonesia Tbk during the period 2021 to 2024. Audit delay is an important issue because it affects the timeliness of financial reporting, which has a direct impact on decision making by stakeholders. This study uses a quantitative approach with a case study method, where secondary data is obtained from audited annual financial statements. Audit delay is measured based on the time difference between the book closing date and the audit opinion date. Financial distress is measured by the Debt to Asset Ratio (DAR), profitability by Return on Assets (ROA), and earnings quality by the ratio of operating cash flow to net income. The results of this study indicate that all three variables have a strong relationship with audit delay: DAR and ROA are positively correlated, while earnings quality is negatively correlated with audit delay. However, the three relationships are not statistically significant at the 5% significance level. This finding indicates that although the direction of the relationship is in accordance with the theory, there is not enough evidence to state a strong influence in general, given the limited amount of data. This study provides an empirical contribution to understanding audit delay and suggests that companies improve transparency and reporting quality to minimize audit delays.